A review of Grevillea (Proteaceae) from New Caledonia with the description of two new species - Majourau, Pauline; Pillon, Yohan (Phytotaxa, 2020)
The taxonomy of Grevillea (Proteaceae) in New Caledonia is reviewed. The names G. deplanchei, G. macmillanii, G. rubiginosa, and G. sinuata are re-instated at the species rank. A new name, G. mondorensis, is provided for the plants previously identified as G. gillivrayi var. glabriflora, and two new species are described, G. nepwiensis and G. vuniana. Second-step lectotypifications are provided for G. heterochroma, G. rubiginosa, and G. vieillardii. This study raises the number of endemic species of Grevillea recognized in New Caledonia from three to ten. An identification key to all species of Grevillea in New Caledonia is provided.